PENGEMBANGAN MEDIA PEMBELAJARAN ONLINE BERBASIS WEBSITE PADA MATERI LISTRIK DINAMIS - Irawan, Bambang; Maria, Haratua Tiur; Mursyid, Syukran (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aims to develop learning media using website, and determinate the feasibility of learning media in the form website. This research is an R & D research that adopts the development of Borg &Gall that has been modified by Sugiono. Subjects in this research are students class IX SMPN 2 Pontianak. The type of data generated is qualitative data which is analyzed by guidance criteria of rating category to determine product quality using Likert scale. The results of this research are; 1) Produce website as a learning media; the product quality that has been developed is "very feasible" with percentage based on expert material appraisal, 75% by media expert equal to 97% and educator of junior high school with percentage equal to 90%; 2) developed learning media used for conceptual change in students using the McNemar test. Obtained a price of  is 16, thus it can be concluded that there?s change misconception.  Keywords: Research and Development, Learning Media, Website